Análise comparativa entre os frameworks de desenvolvimento de aplicativos móveis multiplataforma - Silva, Antônio Eudálio de Sousa da. (2020)
With the advancement in mobile technologies, in parallel there has been an increasing demand for mobile applications, forcing the market to offer good quality products, in the shortest possible time and cost. There are currently two main platforms, Android and iOS. In this work, the comparison was made in relation to the development with Android, with two of the most modern frameworks: React Native and Flutter. This comparison aims to help developers choose the most appropriate framework to use in their projects, as well as solve their problem. In order to make the comparison, a series of criteria was raised based on related works, and, for each of the criteria, a weight was applied in order to determine the level of relevance for the comparison. The criteria were chosen in order to have a general notion of the tool in aspects such as: infrastructure, development, performance and usability. The comparison shows that the two frameworks are capable of meeting the needs of the most diverse projects, which have an engaged community and the tendency is for these frameworks to improve and grow even more in the short / medium term. In addition, among the results is the fact that Flutter stood out in terms of performance and rendering speed, while React Native stands out in terms of technology for using popular technologies such as HTML, CSS and JavaScript that favor the speed of learning and development with the framework.